The Netherlands and the oil crisis : business as usual - Hellema, Duco (Amsterdam archaeological studies., 2004)
This incisive study examines the role of the Netherlands in the October War and the oil crisis of 1973. The authors contend that the actions of the Dutch government were hypocritical: the Dutch government faced a domestic crisis when an oil embargo was le.